1998
DOI: 10.1136/jnnp.65.1.88
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial chondrosarcoma: review of the literature and report of 15 cases

Abstract: The available data in the literature (177 cases), two current clinical patients, and cases which occurred in The Netherlands (13) were reviewed concerning the clinical presentation, pathological features, radiological data, and treatment options of chondrosarcoma of the cranial base. The mean age of patients was 37 years, the male/female ratio 1: 1.1. The most frequent complaints were diplopia with oculomotor disorders (51%), headache (31%), and decreased hearing, dizziness, and tinnitus with statoacusticus dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
101
0
13

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(120 citation statements)
references
References 41 publications
6
101
0
13
Order By: Relevance
“…Intracranial chondrosarcoma typically affects patients in the fourth and fifth decades of life, with no gender preference (7). The clinical presentation of chondrosarcomas has been extensively reported in the literature (8,9). Generally, patients present with an extensive history of headaches and symptoms associated with increased intracranial pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracranial chondrosarcoma typically affects patients in the fourth and fifth decades of life, with no gender preference (7). The clinical presentation of chondrosarcomas has been extensively reported in the literature (8,9). Generally, patients present with an extensive history of headaches and symptoms associated with increased intracranial pressure.…”
Section: Discussionmentioning
confidence: 99%
“…In a review of 192 chondrosarcoma cases by Chandler et al (12), 62% were of the classical subtype, while the mesenchymal and myxoid types accounted for 30 and 8% of cases, respectively. Korten et al (8) reviewed 192 cases of chondrosarcoma and reported that in general, the mesenchymal type is malignant and occasionally spreads to distant areas, while the classical subtype is the most benign of the three subtypes. In this study, a case of classical type intracranial chondrosarcoma that occurred in the left frontal region of the skull was presented, which has rarely been reported in the literature to date.…”
Section: Discussionmentioning
confidence: 99%
“…Chondrosarcomas arise off the midline at the suture line, unlike chordomas that arise from the clivus in the midline. Radiological examination almost always reveals bone destruction and variable degrees of calcification on CT, involvement of the neural and vascular structures on MRI, and mostly hypovascularity on angiography (Korten et al 1998). Occasionally, cyst-like hypodense centres secondary to necrosis can be found (Cohen-Gadol et al 2003).…”
Section: Chordomas and Chondrosarcomasmentioning
confidence: 99%
“…6). These are slowly growing tumours presenting with visual complaints, mainly diplopia, whereas a third of patients complain of headache (Korten et al 1998). Less common presentations include dizziness, tinnitus, facial sensory deficits, ataxia and hemiparesis.…”
Section: Chordomas and Chondrosarcomasmentioning
confidence: 99%
See 1 more Smart Citation